2005
DOI: 10.1007/s10815-005-5145-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type and state of co-culture cells on in-vitro development of porcine oocytes matured and fertilized in vitro

Abstract: As compared with GCs and pOECs at follicular stage, the pOECs at ovulation and CL stages had a better competence to support porcine embryo development under in vitro conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In vivo , fertilization has been shown to occur during this period in equine or porcine species [ 63 , 64 ]. Moreover, porcine oviduct cells have a better competence to support porcine embryo development when they are collected at ovulation or corpus luteum stages than at other ovarian cyclic stages [ 65 ]. Thus, we used oviduct cells collected during the in vivo fertilization period to keep the favourable environment of fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , fertilization has been shown to occur during this period in equine or porcine species [ 63 , 64 ]. Moreover, porcine oviduct cells have a better competence to support porcine embryo development when they are collected at ovulation or corpus luteum stages than at other ovarian cyclic stages [ 65 ]. Thus, we used oviduct cells collected during the in vivo fertilization period to keep the favourable environment of fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Even if this argument is correct, it should be noted that in suboptimal conditions, which are most often present in ART laboratories, coculture systems might eliminate the harmful effects of environmental factors on embryo development. Many studies have reported the beneficial effects of co-cultures on embryo development in vitro in humans [1,32,33]; domestic animals [34,35] and rodents [19,26,27]. However, it is not fully elucidated why co-culture of embryos with somatic cells improves embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method to improve the in vitro development of oocytes and embryos is coculturing with somatic cells (17)(18)(19)(20). However, the use of a feeder layer for improving the IVM of isolated follicles has received less attention (21).…”
mentioning
confidence: 99%